2015
DOI: 10.4041/kjod.2015.45.5.245
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar bone thickness around maxillary central incisors of different inclination assessed with cone-beam computed tomography

Abstract: ObjectiveTo assess the labial and lingual alveolar bone thickness in adults with maxillary central incisors of different inclination by cone-beam computed tomography (CBCT).MethodsNinety maxillary central incisors from 45 patients were divided into three groups based on the maxillary central incisors to palatal plane angle; lingual-inclined, normal, and labial-inclined. Reformatted CBCT images were used to measure the labial and lingual alveolar bone thickness (ABT) at intervals corresponding to every 1/10 of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
54
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 28 publications
9
54
0
Order By: Relevance
“…Tipping movements might cause changes in the alveolar bone 1030. In the present study, we observed decreases in buccal plate thickness (0.6–1.1 mm) and buccal alveolar crest height (1.7–2.2 mm) after MARPE.…”
Section: Discussionsupporting
confidence: 60%
“…Tipping movements might cause changes in the alveolar bone 1030. In the present study, we observed decreases in buccal plate thickness (0.6–1.1 mm) and buccal alveolar crest height (1.7–2.2 mm) after MARPE.…”
Section: Discussionsupporting
confidence: 60%
“…In addition, more proclination was found in mandibular incisors in the thin gingival biotype. In agreement with the results of previous studies, 14,23 the more proclined the mandibular incisor was, the greater the bone thickness of the labial alveolar plate at the apex level tended to be. It could be suggested that tooth inclination affects marginal bone thickness and gingival biotype in the mandibular incisor regions in patients with skeletal Class III malocclusion.…”
Section: Discussionsupporting
confidence: 82%
“…Buccal bone height (BHb) and palatal/lingual bone height (BHp) indicated that the AC-CEJ distances were measured parallel to the long axis of the tooth. These measurements represent the amount of vertical alveolar bone loss [32]. The buccal (aBTb, mBTb) and palatal/lingual (aBTp, mBTp) bone thicknesses were measured at the mid-root and root apex level, perpendicularly to the long axis of the tooth.…”
Section: Measurements Of Bone Height and Thicknessmentioning
confidence: 99%